A Transformation of Islamic Law in Legislation of Domestic Violence (PDKRT) Law in Indonesia - Faizal, Liky (al-'adalah, 2018)
This article aims to study the transformation of Islamic Shari’a values in the foundation of the law legislation in Indonesia. This study is legal-normative in which, in its analyzing phases, it uses both qualitative techniques of primary and secondary legal materials. The findings of this study indicate that the Islamic Shari’a values have been actualized in the laws and regulations in the elimination of domestic violence in Indonesia. Transformation of Islamic Sharia values is conducted through two approaches, namely through the principles of the content of legislation, and actualization through the material legislation.